2022
DOI: 10.3168/jds.2021-21208
|View full text |Cite
|
Sign up to set email alerts
|

Milk feeding level and starter protein content: Effects on growth performance, blood metabolites, and urinary purine derivatives of Holstein dairy calves

Abstract: The objective of this study was to investigate the effects of milk allowances equal to 526 g/d as moderate (MOD) versus 790 g/d of milk dry matter as high (HI), and starter diets containing 18% or 23% crude protein (CP), on growth performance, blood metabolites, and purine derivative (PD) excretion in the urine of dairy calves. A total of 52 female Holstein dairy calves (40.8 kg of body weight) were randomly assigned to the experimental diets. The treatments were (1) moderate milk and 18% CP starter diet (MOD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
(95 reference statements)
1
11
0
1
Order By: Relevance
“…The higher starter CP content, however, increased the urinary PD excretion and hence improved the MPS, suggesting that greater N supplementation may stimulate the ruminal microbes to produce greater mass in young calves. This is in agreement with our previous report [ 20 ], where was shown that a higher starter CP content can provide more organic matter for ruminal microbes which consequently led to a higher MPS in young calves.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The higher starter CP content, however, increased the urinary PD excretion and hence improved the MPS, suggesting that greater N supplementation may stimulate the ruminal microbes to produce greater mass in young calves. This is in agreement with our previous report [ 20 ], where was shown that a higher starter CP content can provide more organic matter for ruminal microbes which consequently led to a higher MPS in young calves.…”
Section: Discussionsupporting
confidence: 94%
“…A spot urine sampling procedure was used to estimate microbial protein synthesis (MPS) in the rumen, which is based on the purine derivatives (PD) excretion in urine. Because it has been stated that bovine milk containing PD interferes with MPS in suckling calves [ 20 ], urinary PD was measured only in post-weaned calves. Urinary creatinine excretion was used to estimate total urine excretion by using the model described here; BW × 26.8/creatinine concentration (mg/L) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The differences in total DMI were likely responsible for most of the improvement in preweaning ADG, as the higher DMI can provide the necessary energy and protein needed for growth [ 20 ]. Additionally, diet structure can also affect the growth performance of calves, with liquid feeds being shown to meet the energy needs of calves better than solid feeds [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Co.) were measured using spectrophotometer (UV-2600i, Shimadzu, Japan) in accordance with the manufacturer's instructions. For allantoin determination the high-performance liquid chromatography as model 10 A high-performance liquid chromatograph (Shimadzu, Kyoto, Japan) equipped with a UV spectrophotometric detector set at 220 nm was used [ 30 ]. The daily endogenous PD was considered to be 705 µmol/kg of BW 0.75 according to previous suggestions in dairy calves [ 31 ].…”
Section: Methodsmentioning
confidence: 99%